Comparative bioactivity evaluation and metabolic profiling of different parts of Duhaldea nervosa based on GC-MS and LC-MS - Zhao, Qian; Li, Yuan; Li, Si; He, Xiaofeng; Gu, Rui (Frontiers in Nutrition, 2023)
Duhaldea nervosa (Wallich ex Candolle) Anderberg has been widely used as medicine and food additive in China for a long history. Its roots, known as Xiaoheiyao, are the mainly used medicinal part, while the other tissues of D. nervosa are ignored as non-medicinal parts despite their high biomass, resulting in a huge waste of resources. To mine and expand the medicinal values of different parts of D. nervosa, metabolic analysis by GC/LC-MS and bioactivity evaluation were performed. Based on the antioxidant activity and correlation analysis, a metabolite-related network was constructed. A total of 45 volatile and 174 non-volatile compounds were identified. Among them, caffeoylquinic acids and derivatives were more abundant in roots and flowers, while coumaroyltartaric acids and derivatives were mainly present in stems and leaves. By multivariate analysis, 13 volatile and 37 non-volatile differential metabolites were found, respectively. In the bioactivity evaluation of different parts, the order of antioxidant capacity was flowers > roots > leaves or stems. The flowers showed the highest FRAP value (354.47μM TE/g DW) and the lowest IC50 values in the DPPH (0.06 mg/ml) and ABTS (0.19 mg/ml) assay, while higher inhibitory activity against α-glucosidase was exhibited by flowers and leaves. This study first established the similarities and differences of phytochemicals and bioactivities in D. nervosa, providing a scientific basis for developing non-medicinal parts and guiding the clinical application of this medicinal and edible herb.